A new species of Lyriothemis Brauer, 1868 from Vietnam and Thailand (Odonata: Libellulidae) - Kompier, Tom; Holden, James; Makbun, Noppadon (Zootaxa, 2021)
Lyriothemis pallidistigma sp. nov. (holotype male: Cat Tien National Park, Dong Nai Prov., southern Vietnam) is described. This species is reminiscent of L. defonsekai van der Poorten, 2009 and L. elegantissima Selys, 1883, but can be separated by the shape of its secondary genitalia and its patterning. Information on its biology and ecology is provided.